Pengaruh Strategi Omaggio Terhadap Kemampuan Menyimak Teks Hikayat Pada Siswa Kelas X SMA Muhammadiyah Kota Sukabumi Tahun Ajaran 2024/2025: The Influence of the Omaggio Strategy on the Ability to Listen to Hikayat TextIn Class X Students of Muhammadiyah High School, Sukabumi CityAcademicYear2024/2025 - Laura Cantika , Salwa; Firdaus, Asep (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Listening skills are basic skills that are important in language learning, but are often underdeveloped due to uninteresting learning methods. In the context of learning Indonesian, especially in listening to fable texts, students often have difficulty understanding the contents of the text in depth. This phenomenon can be caused by low student involvement due to the use of monotonous learning methods and the lack of utilization of technology or media that are relevant to the needs of today's students. Therefore, an innovative approach is needed to increase students' interest and ability in listening. This study focuses on analyzing the extent to which the Omaggio strategy supported by animated video media can provide a significant impact on improving the ability to listen to fable texts in class X students. The purpose of this study was to test the effect of the Omaggio strategy with the help of animated video media on the ability to listen to fable texts of class X students of SMA Muhammadiyah Kota Sukabumi. This study uses a quantitative method in the form of an experiment with a true experimental design involving an experimental group that applies the Omaggio strategy and a control group whose learning uses conventional learning methods. The posttest results showed an average value of the control class of 77.78 with a total score of 2,100, while the experimental class achieved an average value of 84.4 with a total score of 2,280. The t-test showed a significant value (p <0.05), with the calculation results of t_count> t_table, which proves that the Omaggio strategy significantly improves students' listening skills. The difference in total value of 180 and the difference in average value of 6.62 indicate that the Omaggio strategy has a positive influence on the listening skills of fable texts of class X students of SMA Muhammadiyah Kota Sukabumi in the 2024/2025 Academic Year.